Tradisi Barzanji dan Implementasinya di Rantau Parapat - Shela Citra Harahap; Solihah Titin Sumanti; Khoirul Jamil (Local History & Heritage, 2021)
This article aims to explain the History of the Barzanji Tradition. The Barzanji tradition has been carried out since Islam entered Indonesia. It is undeniable that the entry of Islam had a major influence on Bugis culture. Likewise with the tradition of reading Barzanji in the Rantau Parapat community. In society, the reading of Barzanji is usually done on occasions, such as the pilgrimage. But it's not limited to just that commemoration, the Barzanji tradition is also held on various occasions, as a tribute to the achievement of something better. For example, at the time of the birth of a baby, shaving the baby's hair (akikah), circumcision, weddings and other ceremonies at Rantau Parapat. This research is a qualitative research using the historical method. So the steps taken in this research are heuristics (data collection), verification (Source Criticism), interpretation and historiography. In data collection techniques, the authors collect data from two sources, namely primary sources and secondary sources. From the data collection, then the data is analyzed and interpreted based on chronological order.